Optimalisasi Dan Pengembangan Pemasaran Digital Pada UMKM Kalirungkut - Wahyu Dwi Arzaqy; Sumainah Fauziah (Jurnal Pelayanan Hubungan Masyarakat, 2023)
With the rapid development of the era in the digital world, there are quite a lot of MSMEs, especially in Kalirungkut sub-district, which as a whole do not fully understand and know the rapid digital development so that the Group of 85 KKNT MBKM UPN "Veteran" East Java carried out the initiative by holding digital marketing socialization aimed at providing knowledge and being able to carry out digital development for MSMEs themselves. with this socialization, it can create MSMEs that are very modern and simple. Previously, MSMEs in Kalirungkut Village were dominated by MSMEs that were minimal about digital marketing, therefore MSMEs in Kalirungkut Village could with the holding of this socialization can make MSMEs reach a wider target market so as to achieve optimization of digital marketing.